(untitled) (International journal of artificial intelligence, 2026)
This article examines the importance of developing listening and speaking skills through interactive activities in the English classroom. In modern language education, listening and speaking are considered essential components of communicative competence, as they enable learners to understand spoken language and express their ideas effectively in real-life situations. The study highlights the role of interactive activities such as pair work, group discussions, role-plays, interviews, games, problem-solving tasks, and information-gap exercises in improving learners’ oral communication abilities. These activities create a student-centered learning environment, increase motivation, reduce anxiety, and encourage active participation in the lesson. Special attention is given to the pedagogical value of interactive methods in fostering fluency, pronunciation, vocabulary development, listening comprehension, and confidence in speaking. The article also discusses how meaningful classroom interaction helps students develop critical thinking, cooperation, and spontaneous language use. Furthermore, it emphasizes the teacher’s role in selecting appropriate tasks, organizing communicative situations, and providing supportive feedback to ensure effective skill development.